From Single Molecules to Nanoscopically Structured Materials - Basché, Thomas; Müllen, Klaus; Schmidt, Manfred (Advances in Polymer Science,, 2014)
Mechanical Properties of Single Molecules and Polymer Aggregates Rüdiger Berger, Kurt Binder, Gregor Diezemann, Jürgen Gauß, Mark Helm, Katharina Landfester, Wolfgang Paul (Halle), Peter Virnau. Optical Properties of Individual Molecular Aggregates and Nano Particles Thomas Basché, Hans-Jürgen Butt, Gregor Diezemann, Jürgen Gauß, Klaus Müllen, Harald Paulsen, Carsten Sönnichsen, Rudolf Zentel. Structure Formation of Polymeric Building Blocks I: Self-assembly of Copolymers Kurt Binder, Holger Frey, Andreas Kilbinger (Univ. Fribourg), Ute Kolb, Michael Maskos (IMM Mainz), Wolfgang Paul (Univ. Halle), Hans Wolfgang Spiess. Structure Formation of Polymeric Building Blocks II: Complex Polymer Architectures Kurt Binder, Hans Jürgen Butt, Angelika Kühnle, Klaus Müllen, Wolfgang Paul (Univ. Halle), Erwin Schmidt, Manfred Schmidt, Hans Wolfgang Spiess, Thomas Vilgis. Structure Formation of Polymeric Building Blocks III: Polymer Complexes in Biological Applications Kurt Kremer, Heiko Luhmann, Christine Peter, Friederike Schmid, Erwin Schmidt, Manfred Schmidt, Eva Sinner (Univ. of Natural Resources, Vienna), Tanja Weil (Univ. Ulm).